Fertilization rate, hatching rate, and survival rate of Triploid hybrid Catfish, Clarias macrocephalus X Carias gariepinus produced through cold shock treatment. - Dato-on, Kathleen Tamayo
The investigation of the cold shock treatment for triploidy induction in the hybrid catfish from the parental cross the C. macrocephalus male x C. gariepinus female was carried out by subjecting the eggs to a 15-minute temperature shock after one minute post-fertilization to different temperatures ranging from 5 degrees centigrade, 7 degrees centigrade and 9 degrees centigrade. The crucial portion of obtaining a triploid hybrid catfish is on the earliest stage of development. Fertilization, hatching and survival rates were investigated to assure and determine the success of triploidization in the hybrid catfish., Results showed that the exposure of fertilized eggs to cold shock treatment induced triploidy. The highest percentage of triploid fish was obtained in 9 degrees centigrade temperature shock followed by 7 degrees Centigrade temperature shocks. The 5 degrees centigrade and 7 degrees centigrade treatment did not differ significantly on fertilization, hatching and survival rates compared to the 9 degrees centigrade cold shock treatment. On the rate of hatching and survival stages (after yolk sac resorption), no significant difference between the control and the 9 degrees centigrade temperature shock was detected. Therefore, the most suitable cold shock treatment to induce triploidization of the hybrid catfish is at 9 degrees centigrade temperature shock.